2010
DOI: 10.1002/bdrb.20247
|View full text |Cite
|
Sign up to set email alerts
|

Nitrofen induces apoptosis independently of retinaldehyde dehydrogenase (RALDH) inhibition

Abstract: The observed declines in nitrofen-associated retinoic acid signaling appear to be independent of RALDH inhibition and likely result from nitrofen induced cell death/apoptosis. These results support a cellular apoptotic mechanism of CDH development, independent of RALDH inhibition.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
6
0

Year Published

2011
2011
2020
2020

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 16 publications
(6 citation statements)
references
References 57 publications
0
6
0
Order By: Relevance
“…For example, mesenchyme-derived cells normally undergo apoptosis at the pseudoglandular stage (embryonic days 12 – 17); a time frame that corresponds with the studies herein [3537, 45]. In addition, treatment of fetal rat lung explants with the MEK1/2 kinase inhibitor, U0126 or a teratogenic diphenyl ether, nitrofen induced high levels of mesenchymal but not epithelial apoptosis [26, 34]. Moreover, inhibition of insulin-like growth factor-I receptor (IGF-IR) signaling with neutralizing antibodies induced high levels of apoptosis in human fetal lung mesenchyme but not epithelium [46].…”
Section: Discussionmentioning
confidence: 90%
See 1 more Smart Citation
“…For example, mesenchyme-derived cells normally undergo apoptosis at the pseudoglandular stage (embryonic days 12 – 17); a time frame that corresponds with the studies herein [3537, 45]. In addition, treatment of fetal rat lung explants with the MEK1/2 kinase inhibitor, U0126 or a teratogenic diphenyl ether, nitrofen induced high levels of mesenchymal but not epithelial apoptosis [26, 34]. Moreover, inhibition of insulin-like growth factor-I receptor (IGF-IR) signaling with neutralizing antibodies induced high levels of apoptosis in human fetal lung mesenchyme but not epithelium [46].…”
Section: Discussionmentioning
confidence: 90%
“…Since other studies have suggested that different fetal lung cell types undergo apoptosis variably, the distribution of apoptotic cells within the explants was investigated [3437]. The distribution of activated caspase-3 within the explant tissue beds was characterized by whole-mount immunofluorescence confocal microscopy as described above.…”
Section: Resultsmentioning
confidence: 99%
“…The nitrofen-induced CDH model is one of the most widely used animal models to study the pathogenesis of PH in CDH (9,13,15). However, the exact molecular mechanism underlying nitrofeninduced PH in this model is still not fully understood.…”
Section: Discussionmentioning
confidence: 99%
“…The copyright holder for this preprint (which this version posted April 4, 2020. ; https://doi.org/10.1101/2020.04.03.024851 doi: bioRxiv preprint 14 RA signaling is an important regulator of normal diaphragm development and when inhibited causes CDH (Clugston et al, 2010a). Pharmacological inhibition of RA synthesis via administration to pregnant females of nitrofen, a herbicide that inhibits ALDH1A2 (Alles et al, 1995;Mey et al, 2003;Kling et al, 2010), inhibits growth of the PPFs to ultimately cause CDH in embryos (Costlow and Manson, 1981;Nakao and Ueki, 1987). To test whether nitrofen similarly affects PPF proliferation in vitro, we cultured E12.5 PPFs in the presence of 100 µM nitrofen.…”
Section: Genetic and Pharmacological Manipulations That Lead To Cdh In Vivo Cause Decreased Ppf Proliferation In Vitromentioning
confidence: 99%